Irak'ın idari ve sosyal yapısı (661-750) - Güler, Zehra (My University, 2019)
Devletleri sadece siyasi ve askeri teşkilatlar ayakta tutmamaktadır. Bunların yanı sıra idarî yapı ve devletin içinde yaşadığı milletlerin özellikleri de devletlerin bekası için oldukça önemlidir. Irak’ta VII. ve VIII. yüzyıllarda oldukça önemli bir mevkideydi. Dicle ve Fırat nehirlerinin ortasında Mezopotamya bölgesinde yer alan Irak, gerek bulunduğu konumun önemliliği ve gerekse Emevî devletine karşı isyankâr halleriyle araştırılmaya değer bir konudur. Emevîler Irak’ı hâkimiyetleri altına aldıktan sonra bölgede birçok ayaklanmalar meydana gelmiştir. Bu ayaklanmalar neticesinde Irak bölgesini yönetmek güç bir hale gelmekteydi. Emevîler buna çare olarak Hulefâ-yi Râşidîn döneminde olduğu gibi eyaletlere geniş yetkilerle donatılmış valiler göndererek bölgeleri baskı altına almaya çalışmışlardır.Irak valileri, Emevîlere muhalif olan halkı yola getirmek için büyük çaba göstermişlerdir. Irak toplumu çeşitli milletlerden meydana gelmekteydi. Özellikle bu dönemde devletin Arap kökenli olması nedeniyle Araplar oldukça fazlaydı. Bu yüzden valiler de Arapların yaptığı gibi kabilecilik yani ırkçılık politikası gütmüşlerdir. Kabilecilik politikasının bir sonucu olarak mevâliyi bürokrasiden uzak tutmuşlardır. Bunların sonucu olarak, Irak halkı, Emevî otoritesini tanımamış ve devlete karşı Abbâsi ihtilaline destek vererek Emevîlerin sonunu hazırlamışlardır. Valiler, Irak’ı bayındır hale getirmiş ve tarımın ıslah olması için kanallar, bentler, barajlar inşa ederek bölgenin kalkınmasını sağlamışlardır. Irak’ta yeni şehirler inşa edilmiş, dinî ve sivil mimarinin en güzel örnekleri verilmiştir. Valiler bu görevlerini yaparken şehirdeki tüm kurumları organize etmiştir.

States exist with not only their political and military organizations, but their administrative structures and the characteristics of the nations which live in that state are very important for states survival. Iraq, in 8th and 9th centuries was in a very important position. Iraq, located in the Mesopotamian region in the middle of the Tigris and Euphrates rivers, is worth to study because of the importance of its location and the rebellious acts against the Umayyad state. There were many riots in the region after Umayyads took control of Iraq. As a result of these riots, it was difficult to rule Iraq region. The Umayyads sent governors, who were equipped with great authority, to the states and tried to suppress the regions as in the period of Hulefa-yi Rashidin. The governors of Iraq made a great effort to discipline the people who opposed the Umayyads. They to caused a lot of blood to spill accordingly. Iraqi society was composed of various nations. Particularly in this era, as a result of government being Arabic, most of the population was consist of Arabs. Therefore, the governors pursued a policy of tribalism, in other words racism, like Arabs. As a result of their tribalism policy, they did not give enough importance to Mevalies, and this let Mevalies to support Abbasid revolution. Despite of all these, people of Iraq did not recognize authority of the Umayyad and supported the Abbasid revolution against the government and brought an end to the Umayyad’s authority. The governors made their regions cultivated and built canals, dams and barrages to improve the agriculture and provided development of their regions. In Iraq, new cities were built and construction of structures such as palaces and masjids ensured the development of the region. The governors also used the benefits of auxiliary foundations. These officers were assigned by the governer and the caliph. These were the protectors of the state for the peace of the people and the state.
Keywords: Administrative Structure; Emevi; Governor; History; Irak; Iraq; İdari Yapı; Kabilecilik; Social Live; Sosyal Hayat; Tarih; Tribalism; Umayyad; Vali